PENGARUH BUDAYA KERJA DAN FASILITAS KERJA TERHADAP KOMITMEN KARYAWAN PT. SEWINDU TIARA SAKTI PALEMBANG - Putri Ramadona; Deva Lessana Putri; Sugeng Mianto Fane (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2021)
Employees and companies are two things that can not be separated. Employees play a major role in running the life of the company and active actors in every activity of the organization. The wheel of company life will be better if the company provides adequate facilities that can support employee commitment. Commitment is an attitude of willingness to uphold the vision, mission and willingness to exert all efforts in carrying out the task. Employee commitment will not grow by itself, there is a significant relationship between work culture and employee commitment The purpose of this study is